Decoy-State and Purification Protocols for Superior Quantum Key Distribution with Imperfect Quantum-Dot-Based Single-Photon Sources: Theory and Experiment - Yuval Bloom; Yoad Ordan; Tamar Levin; Kfir Sulimany; Eric G. Bowes; Jennifer A. Hollingsworth; Ronen Rapaport (PRX Quantum)
The original proposal of quantum key distribution (QKD) was based on ideal single-photon sources, which, 40 years later, are still challenging to develop. Therefore, the development of decoy-state protocols using weak coherent states (WCS) from lasers set the frontier in terms of secure-key rates and distances. Here, we propose and experimentally demonstrate two simple-to-implement QKD protocols that allow practical far from ideal sub-Poissonian photon sources to outperform state-of-the-art WCS. By engineering the photon statistics of a biexciton-exciton cascade in room-temperature single-photon sources based on giant colloidal quantum dots coupled to nanoantennas, we show that either a truncated decoy-state protocol or a heralded-purification protocol can be employed to achieve a significantly increased performance in terms of the maximal allowed channel loss for secure-key creation, which can exceed even that of ideal WCS by more than 3 dB. We then experimentally emulate a BB84 QKD using such a quantum dot source, verifying the superiority of our protocols over the best possible BB84 WCS performance. These protocols can be utilized efficiently on a host of various quantum emitters having controllable photon statistics with a finite photon-number basis, offering a practical approach to QKD without the hindering requirements on the single-photon purity of the photon source.